Alliances and Survival of New Biopharmaceutical Ventures in the Wake of the Global Financial Crisis. (1st April 2019) - Xia, Tianjiao; Dimov, Dimo
Abstract : Engaging in exploration and exploitation is essential to business survival and performance. While firms manage exploration and exploitation alliances for the long‐term, how prepared are they for sudden shocks in the short‐term? We address this question in the context of a unique and opportune natural experiment associated with the 2008 financial crisis. Our analysis of 155 new biopharmaceutical ventures over a seven‐year period suggests that exploration alliances—with a long‐term orientation—make a firm more vulnerable to external shocks. In contrast, exploitation alliances as well as a balance between exploration and exploitation alliances—which underlie short‐term performance—enable the firm to sustain external shocks.